1976
DOI: 10.1021/bi00665a030
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence depolarization studies of phase transitions and fluidity in phospholipid bilayers. 2. Two-component phosphatidylcholine liposomes

Abstract: The fluorescence deplorarization associated with the hydrophobic fluorescent probe 1,6-diphenyl-1,3,5-hexatriene is used to monitor changes in fluidity accompanying the gel-liquid crystalline phase transition in phosphatidylcholine dispersions. In this way, the parameters of the phase transition are determined for both large, multilamellar liposomes and small, single-lamellar vesicles composed of three mixtures of phosphatidycholines: dimyristoyl-dipalmitoyl, dimyristoyl-distearoyl, and dioleyl-dipalmitoyl. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
256
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 504 publications
(294 citation statements)
references
References 33 publications
36
256
0
1
Order By: Relevance
“…It was shown that DOPC and DPPC are not miscible at room temperature (23). As shown above, our imaging study has provided new details about the miscibility.…”
Section: Resultssupporting
confidence: 60%
“…It was shown that DOPC and DPPC are not miscible at room temperature (23). As shown above, our imaging study has provided new details about the miscibility.…”
Section: Resultssupporting
confidence: 60%
“…In contrast, molecular dynamics (MD) simulations pointed to an increasing diffusion coefficient with increasing vesicles size with the highest value for planar bilayers (7). Other properties, such as fusion rate (18, 23), phase transition temperature (19,24,25), and elasticity (20), have been shown to vary for vesicles of different sizes.NMR studies can provide a great deal of information on bilayer dynamics and order parameters. They have been used to investigate the effect of vesicle curvature on the dynamics of lipid acyl chains.…”
mentioning
confidence: 99%
“…However, in a biological membrane, microenvironments of different dielectric constants could also be formed along the membrane plane due to the presence of cholesterol and protein molecules and to microdomains of specific phospholipid composition. In this respect, DPH is a useful probe, since it partitions equally between fluid and solid environments, insuring a homogeneous distribution in the membrane plane [40]. The DPH lifetime distribution width as a function of temperature in liposomes of extracted phospholipids showed a pattern similar to that of the erythrocyte membrane.…”
Section: Discussionmentioning
confidence: 90%